Screening for subtelomeric rearrangements in 210 patients with unexplained mental retardation using multiplex ligation dependent probe amplification (MLPA). Issue 12 (9th December 2004) - Koolen, D A; Nillesen, W M; Versteeg, M H A; Merkx, G F M; Knoers, N V A M; Kets, M; Vermeer, S; van Ravenswaaij, C M A; de Kovel, C G; Brunner, H G; Smeets, D; de Vries, B B A; et al.
Abstract : Background: Subtelomeric rearrangements contribute to idiopathic mental retardation and human malformations, sometimes as distinct mental retardation syndromes. However, for most subtelomeric defects a characteristic clinical phenotype remains to be elucidated. Objective: To screen for submicroscopic subtelomeric aberrations using multiplex ligation dependent probe amplification (MLPA). Methods: 210 individuals with unexplained mental retardation were studied. A new set of subtelomeric probes, the SALSA P036 human telomere test kit, was used. Results: A subtelomeric aberration was identified in 14 patients (6.7%) (10 deletions and four duplications). Five deletions were de novo; four were inherited from phenotypically normal parents, suggesting that these were polymorphisms. For one deletion, DNA samples of the parents were not available. Two de novo submicroscopic duplications were detected (dup 5qter, dup 12pter), while the other duplications (dup 18qter and dup 22qter) were inherited from phenotypically similarly affected parents. All clinically relevant aberrations (de novo or inherited from similarly affected parents) occurred in patients with a clinical score of ⩾3 using an established checklist for subtelomeric rearrangements. Testing of patients with a clinical score of ⩾3 increased the diagnostic yield twofold to 12.4%. Abnormalities with clinical relevance occurred in 6.3%, 5.1%, and 1.7% of mildly, moderately, and severely retarded patients, respectively, indicating that testing for subtelomeric aberrations among mildly retarded individuals is necessary. Conclusions: The value of MLPA is confirmed. Subtelomeric screening can be offered to all mentally retarded patients, although clinical preselection increases the percentage of chromosomal aberrations detected. Duplications may be a more common cause of mental retardation than has been appreciated.